PENGARUH CR, DER, ROE, TATO DAN NPM TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2018-2021 - Yosi Aprilani Br Perangin Angin; Vilonika Br Napitupulu; Hotma Ria Br Regar; Herlin Munthe; Siswanto; Melfrianti Romauli Purba (Journal Accounting International Mount Hope, 2024)
This research aims to see the influence of CR,DER,ROE,TATO and NPM on Share Prices in Pharmaceutical Sub-sector Companies listed on the Indonesia Stock Exchange for the 2018- 2021 period. The type of research used for this research is Quantitative Research. The data Source in this research is secondary research. This research population was obtained from 9 companies listed on the indonesian Stock Exchange. And the samples used in this research were 36 samples. The data collection technique used in this research is using Documentation Techniques to collect secondary data from the Annual Financial Reports of the Pharmaceutical Sub Sector for the period 2018-2012. Based on the partial and simultaneous results of this research, the variables X Current Ratio (CR), Debt To Equity Ratio (DER), Return On Equity (ROE) and Total Assets Turnover (TATO) have a significant effect on Variable Y Stock Prices. The results of the coefficient of Determination show that the independent variables (X) influence the Dependent Variable (Y). In this study it was 37.0%. This means that the remaining 50.7% is influenced by other variables.